Influence of work rate on dynamics of O2 uptake under hypoxic conditions in humans - Hotta, N.; Abe, D.; Yoshida, T.; Aoki, T.; Fukuoka, Y. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: It was the purpose of the investigation to determine whether an altered work rate could influence the oxygen uptake (V.O2) and heart rate (HR) dynamics at hypoxia and normoxia. Methods: Ten males performed a cycle exercise with 2 repetitions of 6 min each at a constant work load while breathing one of two inspiratory O2 fractions (FIO2): 0.12 (moderate hypoxia) and 0.21 (normoxia). Each test began with unloaded pedaling. This was followed by three constant loads, which were 40%, 60%, and 80% of the subject's gas exchange threshold (GET) in hypoxia (FIO2 = 0.12), with the 80% GET load repeated under normoxia (room air). V.O2 was measured on a breath-by-breath basis and beat-by-beat HR via ECG, and the half time (t1/2) of each parameter was established, following interpolation data. Results: There were no remarkable differences in t1/2 V.O2 dynamics among the 40%, 60% and 80% GET; however, the differences became significant at hypoxia compared with normoxia. The HR dynamics were significantly faster in normoxia compared with hypoxia, independent of work rates. During steady-state exercise, the alterations in HR and cardiac output (Q) using the acetylene rebreathing method depended on increases in the work rate, and a significantly increase in at 80% GET was observed when compared with normoxia. Increases of stroke volume (SV) were unaffected by altered work rates and inspired O2 concentrations. The arteriovenous oxygen difference (Ca-vO2) at a steady-state of exercise increased proportionally with the work rate under hypoxia, and a much greater Ca-vO2 was observed during normoxic exercise than under hypoxia. Conclusion: These results seem to suggest that in humans, O2 uptake dynamics are affected by lower O2, not by changing work rates at hypoxia, to which the interaction between lower O2 utilization in exercising muscles and hypoxic-induced greater blood flow can be attributed.